Evaluation of concrete strength by non-destructive methods - Balakrishna, M. N.; Jayaramappa, N. (Journal of Structural Engineering, 2025)
There are many test methods to assess concrete in situ such us Non-destructive test methods (Schmidt hammer and Ultrasonic Pulse Velocity), and these methods consider indirect and predicted tests to determine concrete strength in situ, whereas these tests affected by many parameters which depend on the nature of materials used in production of concrete. So, there is a difficulty in determining strength of hardened concrete in situ precisely by this method. This research aim to find unified relationship in order to connect the results of these tests and correlate them with the results of crushing strength of cubes by using statistical methods in the analyzing process depending on laboratory tests carried on concrete cubes with different mixing ratios and curing conditions, and finding correlation curves to predict the strength of concrete much better. This research also presents an investigation to determine the reliability of several non-destructive test (NDT) methods on concrete cube. The NDT test methods evaluated in the test include: rebound hammer test and Ultrasonic pulse velocity test. The test variable was the grade and age of concrete. In this research totally seventy two concrete cubes of size (150 × 150 × 150) mm with different grades of concrete strength such as 25, 30, 35, and 40 N/mm2 were prepared and tested at the ages of 7, 14, and 28 day. It was confirmed from test results that, the investigation techniques available in this research were considered adequate and reliable enough for strength assessment of the concrete cube. However non-destructive tests did not applied directly by using the manufacturer calibration chart but instead of that more reliable calibration charts needs to be established. It was also concluded from the test results that, investigation should be carried out by experienced and competent engineers who understand the strength and limitations of the various techniques. Finally the results show that the Linear regression analysis is the best fit for the compressive strength prediction relationship by using Rebound hammer and Ultrasonic pulse velocity test on concrete cube for different age and grade of concrete.